1987
DOI: 10.1152/jn.1987.58.2.251
|View full text |Cite
|
Sign up to set email alerts
|

Use-dependent block of excitatory amino acid currents in cultured neurons by ketamine

Abstract: 1. Mouse hippocampal neurons grown in dissociated cell culture were patch clamped using a whole cell voltage clamp (discontinuous switching clamp) technique. The currents generated by pressure applications of excitatory amino acids were studied over a wide range of holding potentials, and current-voltage curves were plotted. Excitatory amino acids that activated the N-methyl-D-aspartic acid (NMDA) receptor demonstrated some degree of desensitization with repeated applications, whereas the currents observed in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

15
154
0
1

Year Published

1989
1989
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 336 publications
(175 citation statements)
references
References 0 publications
15
154
0
1
Order By: Relevance
“…2 B, C1). The binding characteristics are similar to those described for some of the voltage-dependent blockers of NMDA receptor (MacDonald et al, 1987;Huettner and Bean, 1988). The extent of agonist dependency affects the degree to which the blocker is trapped in the channel, so the blockers range from those that are not trapped [e.g., 9-aminoacridine (Benveniste and Mayer, 1995)] to those that are fully trapped [e.g., MK-801 (Huettner and Bean, 1988)].…”
Section: ␣5␤s Is a Use-dependent Nmda Receptor Inhibitorsupporting
confidence: 54%
“…2 B, C1). The binding characteristics are similar to those described for some of the voltage-dependent blockers of NMDA receptor (MacDonald et al, 1987;Huettner and Bean, 1988). The extent of agonist dependency affects the degree to which the blocker is trapped in the channel, so the blockers range from those that are not trapped [e.g., 9-aminoacridine (Benveniste and Mayer, 1995)] to those that are fully trapped [e.g., MK-801 (Huettner and Bean, 1988)].…”
Section: ␣5␤s Is a Use-dependent Nmda Receptor Inhibitorsupporting
confidence: 54%
“…In support of this we have found that when 100p1M L-alanine, a rapidly dissociating agonist , is used to activate the glycine recognition site, the kinetics of action of CPP are similar to those measured with 3 pm glycine. The slow recovery from antagonism of NMDA receptor responses evoked by cyclic antagonists could alternatively have a component due to channel block, since drugs such as MK-801, ketamine and desipramine (MacDonald et al, 1987;Huettner & Bean, 1988;Sernagor et al, 1989), which block the ion channel of NMDA receptors, exhibit similar slow kinetics. For this class of drugs both the rate of recovery from block, and potency at equilibrium, show strong voltage dependence.…”
Section: Discussionmentioning
confidence: 99%
“…It has been established that dissociative anesthetics are noncompetitive inhibitors of NMDA excitatory ligand-gated ion channels (Lodge and Anis, 1982;Anis et al, 1983;MacDonald et al, 1987MacDonald et al, , 1991ffrench-Mullen and Rogawski, 1989;Rogawski and Wenk, 2003). These drugs also modulate the activity of nicotinic acetylcholine, muscarinic, and opioid receptors, and voltage-gated ion channels, but at significantly higher concentrations than needed to block NMDA receptors (Finck and Ngai, 1982;Ramoa et al, 1990;Hustveit et al, 1995;Hirota and Lambert, 1996;Scheller et al, 1996;Brau et al, 1997;Furuya et al, 1999;Flood and Krasowski, 2000;Yamakura et al, 2000;Schnoebel et al, 2005).…”
Section: Introductionmentioning
confidence: 99%